2013
DOI: 10.1186/cc13071
|View full text |Cite
|
Sign up to set email alerts
|

Role of calcium desensitization in the treatment of myocardial dysfunction after deep hypothermic circulatory arrest

Abstract: IntroductionRewarming from deep hypothermic circulatory arrest (DHCA) produces calcium desensitization by troponin I (cTnI) phosphorylation which results in myocardial dysfunction. This study investigated the acute overall hemodynamic and metabolic effects of epinephrine and levosimendan, a calcium sensitizer, on myocardial function after rewarming from DHCA.MethodsForty male Wistar rats (400 to 500 g) underwent cardiopulmonary bypass (CPB) through central cannulation and were cooled to a core temperature of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…With respect to Ca 2ϩ sensitizers, we are unaware that any have been shown to unequivocally target TnI phosphorylation. In previous studies, we (6) and others (27) found that the Ca 2ϩ sensitizer levosimendan improves the pressure/volume relationship of the heart after H/R in an in vivo rat model. Most studies indicate that levosimendan exerts its positive inotropic effects by targeting Ca 2ϩ binding to cTnC or by inhibiting phosphodiesterase 3 (PDE3) breakdown of cAMP (9, 23).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…With respect to Ca 2ϩ sensitizers, we are unaware that any have been shown to unequivocally target TnI phosphorylation. In previous studies, we (6) and others (27) found that the Ca 2ϩ sensitizer levosimendan improves the pressure/volume relationship of the heart after H/R in an in vivo rat model. Most studies indicate that levosimendan exerts its positive inotropic effects by targeting Ca 2ϩ binding to cTnC or by inhibiting phosphodiesterase 3 (PDE3) breakdown of cAMP (9, 23).…”
Section: Discussionmentioning
confidence: 76%
“…Most studies indicate that levosimendan exerts its positive inotropic effects by targeting Ca 2ϩ binding to cTnC or by inhibiting phosphodiesterase 3 (PDE3) breakdown of cAMP (9, 23). Rungatscher and colleagues (27) reported that levosimendan mitigated the H/R-induced increase in cTnI phosphorylation and suggested that this was the underlying mechanism of enhanced contractility in their in vivo rat model. However, based on this result, we conducted experiments exploring the effects of levosimendan on cTnI phosphorylation in isolated cardiomyocytes, but could not confirm that levosimendan had any mitigating effect on the H/R-induced increase in cTnI phosphorylation.…”
Section: Discussionmentioning
confidence: 97%
“…The latter is indeed an essential component of ECC circuits in clinical setting [ 19 ]. Both CPB and ECMO are based on the performance of oxygenator to support circulatory and respiratory functions during cardiac surgery operations or critical cardiorespiratory diseases, respectively [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The inotropic and lusitropic effects of levosimendan at low concentrations (nM) have been attributed to Ca 2+ sensitization and phosphodiesterase3 inhibition mechanisms [8]. As it acts in a very specific manner, levosimendan has been found to achieve satisfactory preconditioning and positive inotropic effects without Ca 2+ overload, thereby improving survival rates among adult heart failure patients [9, 10].…”
Section: Introductionmentioning
confidence: 99%